Tectonic Fabric, Geochemistry, and Zircon-Monazite Geochronology as Proxies to Date an Orogeny: Example of South Delhi Orogeny, NW India, and Implications for East Gondwana Tectonics - Singh, Subhash; De Waele, Bert; Shukla, Anjali; Umasankar, B. H.; Biswal, Tapas Kumar (Frontiers in Earth Science, 2021)
We have dated the South Delhi orogeny, Aravalli-Delhi Mobile Belt (ADMB), NW India, using the tectonic fabric, geochemistry, and zircon-monazite geochronology as the proxies. The South Delhi Terrane (SDT), a passive margin domain in the ADMB, consists of multiply deformed (D1–D4) greenschist facies rocks and several granite plutons. The D1 deformation is characterized by pervasive isoclinal recumbent F1 fold and axial planar tectonometamorphic fabric, S1, developed in all rock types. The S1 minerals belong to peak greenschist facies metamorphism, M1, suggesting syntectonic nature of M1 with D1. The age of the D1-M1 is constrained by the syncollisional peralkaline S type Sewariya granite which is characterized by magmatic/submagmatic fabric (Sm) coplanar with the S1. The margin of the pluton is turned into quartzofeldspathic gneiss carrying the evidence of high temperature deformation. The age of Sewariya granite is estimated at ca. 878 Ma by zircon geochronology. The D1-M1 is further constrained by monazite geochronology of the mica schist at ca. 865–846 Ma. The other granite plutons and metarhyolite are pre-D1 and emplaced at ca. 992–946 Ma. The D2 deformation produced NE-SW trending open upright F2 folds coaxial with the F1, and northwesterly vergent F2–axial planar thrusts. Monazite geochronology constrains the D2 at ca. 811–680 Ma. The D3 is characterized by small to large scale NW-SE folds, and the D4 by faults and fractures marking the brittle deformation in the rocks. The D4 is constrained by monazite geochronology at ca. 588–564 Ma. There are upper amphibolitic tectonic slivers along the D2-Phulad thrust, belonging to the pre-Delhi rocks, which show ca. 1,638 Ma metamorphism age. From the above study, it is suggested that the South Delhi orogeny belongs to ca. 878–680 Ma marking the final amalgamation of Marwar Craton with the rest of India. This overlaps the early phase of the Pan-African orogeny (900–630 Ma). The brittle deformation, D4, coincides with Kuunga orogeny (650–500 Ma). Our study implies that India, like other continents in the East Gondwana, underwent amalgamation of internal blocks until the late part of the Neoproterozoic.